Faktor Yang Berhubungan Dengan Kejadian Nyeri Haid (Dysmenorrhea Primer) Pada Mahasiswi Fakultas Agama Islam Universitas Muslim Indonesia Dalam Merancang Aplikasi Dysmenorrhea Insights - Triya; Arman; Hasriwiani Habo Abbas (Window of Public Health Journal, 2026)
Primary dysmenorrhea is pain that occurs before or during menstruation without any pathological abnormalities in the reproductive organs. This condition can cause discomfort, disrupt learning, and affect daily activities among female students. Understanding these factors is crucial for developing effective interventions. This study aims to determine the factors associated with the occurrence of menstrual pain (primary dysmenorrhea) in female students of the Faculty of Islamic Studies, Muslim University of Indonesia, as a basis for designing the Dysmenorrhea Insights application. This study used a quantitative, cross-sectional design. The study population comprised 143 female students, and a sample of 105 respondents was obtained using the Slovin formula. Data collection was carried out using a questionnaire. Data analysis was conducted using univariate and bivariate methods, and the results are presented in tabular and narrative form. The results showed no relationship between age at menarche and the occurrence of primary dysmenorrhea (p = 0.414). Meanwhile, there was a relationship between menstrual cycle (p = 0.044), menstrual duration (p = 0.040), stress level (p = 0.026), diet (p = 0.031), and family history (p = 0.001) and the occurrence of primary dysmenorrhea. Based on the study results, it is recommended that female students pay more attention to factors proven to be associated with menstrual pain, such as menstrual cycle, duration, stress level, diet, and family history, to reduce the risk of primary dysmenorrhea, which can disrupt daily activities and learning.